2008
DOI: 10.1093/pasj/60.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku Discovery of Hard X-Ray Pulsations from a Rotating Magnetized White Dwarf, AEAquarii

Abstract: A fast rotating magnetized white dwarf, AEAquarii, was observed with Suzaku, in 2005 October–November and 2006 October with exposures of 53.1 and 42.4 ks, respectively. In addition to clear spin modulation in the 0.5–10 keV band of the XIS data at the barycentric period of 33.0769$\pm$0.0001 s, the 10–30 keV HXD data in the second half of the 2005 observation also showed statistically significant periodic signals at a consistent period. On that occasion, the spin-folded HXD light curve exhibited two sharp spik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 48 publications
4
92
2
Order By: Relevance
“…It is illuminating to compare x 1 CMa with the degenerate X-ray pulsars, namely white dwarfs and neutron stars [63][64][65] . Some neutron star X-ray pulsars have a thermal component in their X-ray spectra, which is explained as originating from their atmosphere 66 .…”
Section: Discussionmentioning
confidence: 99%
“…It is illuminating to compare x 1 CMa with the degenerate X-ray pulsars, namely white dwarfs and neutron stars [63][64][65] . Some neutron star X-ray pulsars have a thermal component in their X-ray spectra, which is explained as originating from their atmosphere 66 .…”
Section: Discussionmentioning
confidence: 99%
“…This places the white dwarf in AE Aquarii in the same category as the rotational power pulsars, which shows a similar ratio of X-ray luminosity to spin-down power (e.g. [73,74]). From a model independent energetics point it can be shown that the fast rotation period, combined with an inferred magnetic field strength of B * ∼ 10 6 G based on circular polarization measurements (e.g.…”
Section: Ae Aquarii: a Rapidly Asynchronous Propeller Driven Pulsarmentioning
confidence: 78%
“…This implies that the low mass accretion and rapid rotation of the highly magnetized white dwarf may provide a mechanism for pulsar-like particle acceleration and nonthermal emission. Recent results from Suzaku X-ray satellite (Terada et al 2008) showed a non-thermal spectrum at energies x ≥ 10 keV. It has been showed recently (e.g. )…”
Section: Spin-down and Particle Accelerationmentioning
confidence: 79%